A new source parameters estimation method of airborne gravity gradient tensor data. Issue 1 (1st December 2016) - Zhou, Shuai; Jiao, Jian
Abstract : One of the important tasks of potential field interpretation is source parameters estimation of the geological structures, including the horizontal position and buried depth. A new method to interpret airborne gravity tensor data is proposed in this paper based on Normalized Downward Continuation (NDC) of the tensor data directional total horizontal derivatives. The NDC method was introduced for source depth estimation, which can be applied to analytical signal modulus and potential fields themselves. And the maxima of the NDC map mainly correspond to the centre location of the geologic source. We applied the NDC method to the directional total horizontal derivatives which can be used for delineating the sources' horizontal edges. The maximum values of the result indicate the source edges horizontal position and buried depth simultaneously. During the calculation, the iteration method of the downward continuation is used in the NDC calculation process to improve the stability. The new method was tested on synthetic models and obtained satisfactory results. Compared with previous work, this new approach has a better lateral resolution.